O arco da memória : literatura e história em A sétima vez, de Alina Paim - Sampaio, Ninalcira de Lemos (2012)
To remind, from French ´´se souvenir´´, give to us the idea, taken from its etymology, to surface what was submerged. And were pulling by the memory distant origins from childhood and juvenile times that the character Teodoro, in Alina Paim.s book ``A Sétima Vez´´ [``The Seventh Time´´], has surface his reminiscences. In his overture, at sixty-seven years old, in a period when the country was faced by a strong political repression that try to vedate any inquirer discurse about the history of the nation, this character begin to invalidate the prejudice still in course that restrincts the old age to the absence of desire, to the rigidity of actions and ideas, to the improductivity and to the lonely wait of the death, and decided to speak. This dissertational work proposes the hypothesis that the report written by Teodoro is a testemony about what it was to live under the age of repression in the brazilian militar dictatorship. By this reason, it is registered in the list of the Trauma Literature (SELLIGMANN-SILVA, 2003). Searching in the past the posible explanations to a phenomenon that happens with him, Teodoro makes use of the colective memory because he pursuits in his relationship with the family, friends and people of his childhood.s city the constitution of his identity and the explanation about what is happen un the actual days, precisely in the first part of the book, ``Eu, Teodoro´´ [``I, Teodoro´´]. In this dissertation, we intent to analyze this novel from the mobile memory (ARRIGUCCI JR., 1987), as traced by Ecléa Bosi (1994) in her work about memories of the old people [``Memória e Sociedade: Lembranças dos Velhos´´] and by Renato Franco and Márcio Selingmann-Silva (2003) and the disaster literature adopted in the book ``História, Memória e Literatura O Testemunho na Era das Catástrofes´´ [``Históry, Memory and Literature The testimony in the Age of catastrophes´´].